Реакция упругой системы консоль – стержень на действие квазистатической и ударно-волновой нагрузок - Аникьев, И.И.; Максимюк, В.А.; Михайлова, М.И.; Сущенко, Е.А. (Прикладная механика, 2014)
A process of deformation of elastic system “console – rod” is experimentally studied under action of a shock wave on a surface of console and under quasi-static loading the console. Registration of quasi-static and non-stationary strains is carried out by PC with use of the high-precision portative eight-canal apparatus LMS SCADAS Mobile (Belgium). It is revealed that in the case of theoretical analysis of analogous problems the nonlinear statement is necessary. Експериментально досліджено процес деформування пружної системи консоль – стержень при дії ударної хвилі на поверхню консолі, а також при квазістатичному її навантаженні. Реєстрація квазістатичних та нестаціонарних деформацій проведена на персональному комп’ютері використанням високоточної портативної восьми канальної апаратури LMS SCADAS Mobile (Бельгія). Виявлено, що при теоретичному аналізі подібних задач необхідна нелінійна постановка.